Structure of an Atmospheric River Over Australia and the Southern Ocean: II. Microphysical Evolution. Issue 18 (22nd September 2020) - Finlon, Joseph A.; Rauber, Robert M.; Wu, Wei; Zaremba, Troy J.; McFarquhar, Greg M.; Nesbitt, Stephen W.; Schnaiter, Martin; Järvinen, Emma; Waitz, Fritz; Hill, Thomas C. J.; DeMott, Paul J.
Abstract: An atmospheric river affecting Australia and the Southern Ocean on 28–29 January 2018 during the Southern Ocean Clouds, Radiation, Aerosol Transport Experimental Study (SOCRATES) is analyzed using nadir‐pointing W‐band cloud radar measurements and in situ microphysical measurements from a Gulfstream‐V aircraft. The AR had a two‐band structure, with the westernmost band associated with a cold frontal boundary. The bands were primarily stratiform with distinct radar bright banding. The microphysical evolution of precipitation is described in the context of the tropical‐ and midlatitude‐sourced moisture zones above and below the 0°C isotherm, respectively, identified in Part I. In the tropical‐sourced moisture zone, ice particles at temperatures less than −8°C had concentrations on the order of 10 L −1, with habits characteristic of lower temperatures, while between −8°C and −4°C, an order of magnitude increase in ice particle concentrations was observed, with columnar habits consistent with Hallett‐Mossop secondary ice formation. Ice particles falling though the 0°C level into the midlatitude‐sourced moisture region and melting provided "seed" droplets from which subsequent growth by collision‐coalescence occurred. In this region, raindrops grew to sizes of 3 mm and precipitation rates averaged 16 mm hr −1 . Plain Language Summary: Atmospheric rivers (ARs) are long, narrow zones of enhanced horizontal poleward water vapor transport that have profound effects on the global hydrological cycle. This and a companion study are the first to analyze an AR affecting Australia and the Southern Ocean through an observational and modeling approach, respectively. There were two precipitation bands associated with the AR, which were primarily stratiform in character with an enhancement of radar reflectivity near the melting level. Part I showed that moisture in the upper part of the AR (above the 0°C level) was primarily sourced from the tropics, while moisture in the lower part (below the 0°C level) was primarily sourced from the middle latitudes. The microphysical evolution of precipitation through these two zones from cloud top to the ground within this AR is investigated. Ice particles forming and growing at altitudes above the 0°C level served as the "seeds" that allowed for further growth below the 0°C level as they melted and collided with droplets. The concentrations, shapes, and size distributions of the ice particles falling through each zone are presented and related to microphysical growth processes occurring within the bands. Key Points: The physical structure and microphysical properties of a summer austral atmospheric river are described Ice particle concentrations increased to >100 L −1 in the zone from −8°C to −4°C, consistent with secondary ice formation Ice particles falling from the tropical‐sourced moisture stream aloft trigger coalescence below the 0°C isotherm